2005
DOI: 10.1111/j.1471-4159.2004.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of tissue plasminogen activator in methamphetamine‐related reward and sensitization

Abstract: In the central nervous system, tissue plasminogen activator (tPA) plays a role in synaptic plasticity and remodeling. Our recent study has suggested that tPA participates in the rewarding effects of morphine by regulating dopamine release. In this study, we investigated the role of tPA in methamphetamine (METH)-related reward and sensitization. Repeated METH treatment dose-dependently induced tPA mRNA expression in the frontal cortex, nucleus accumbens, striatum and hippocampus, whereas single METH treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 57 publications
(100 reference statements)
8
60
0
Order By: Relevance
“…The effect of repeated methamphetamine treatment on tPA mRNA expression in the NAc was dose-dependent and was completely blocked by pretreatment with either the dopamine D1 receptor antagonist R(+)-SCH23390 or dopamine-D2-receptor antagonist reclopride. We confirmed that repeated methamphetamine treatment significantly increased tPA activity in the NAc compared with the saline-treated group, although single methamphetamine treatment had no effect (32). On the other hand, Hashimoto et al (33) demonstrated that a single injection of psychostimulants, including methamphetamine, cocaine, and phencyclidine, induced tPA mRNA expression in the medial and insular prefrontal cortex and the piriform cortex using in situ hybridization histochemistry.…”
Section: A Role For Tpa In Methamphetamine Dependencesupporting
confidence: 61%
“…The effect of repeated methamphetamine treatment on tPA mRNA expression in the NAc was dose-dependent and was completely blocked by pretreatment with either the dopamine D1 receptor antagonist R(+)-SCH23390 or dopamine-D2-receptor antagonist reclopride. We confirmed that repeated methamphetamine treatment significantly increased tPA activity in the NAc compared with the saline-treated group, although single methamphetamine treatment had no effect (32). On the other hand, Hashimoto et al (33) demonstrated that a single injection of psychostimulants, including methamphetamine, cocaine, and phencyclidine, induced tPA mRNA expression in the medial and insular prefrontal cortex and the piriform cortex using in situ hybridization histochemistry.…”
Section: A Role For Tpa In Methamphetamine Dependencesupporting
confidence: 61%
“…Pharmacologic inhibition of tPA in the NAc reduces morphineinduced dopamine release (Nagai et al, 2005b). We also demonstrated that tPA is involved in the rewarding effect of methamphetamine (Nagai et al, 2005a). These findings suggest that the tPA-plasmin system amplifies the rewarding effects of drugs of abuse, by regulating dopamine release in the NAc (Yamada et al, 2005).…”
Section: Introductionmentioning
confidence: 66%
“…The present study firmly consolidates these data and points to an important role of the plasmin system in chronic cocaine. Other studies have shown that the plasmin system releases dopamine in the NAc upon psychostimulants, which activates long-term synaptic plasticity and remodeling, and acutely participates in the rewarding effects of drugs such as methamphetamine or morphine [13,14,16,17,69]. It has been shown that tPA regulates nicotine-induced reward and dopamine release through protease activated receptor-1 [70].…”
Section: Discussionmentioning
confidence: 99%